2022
DOI: 10.1111/mec.16499
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome resequencing reveals signatures of rapid selection in a virus‐affected commercial fishery

Abstract: The spread of infectious diseases is recognized as one of the most pressing global threats to biodiversity and ecosystem function

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 125 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that adaptation to culture environments can occur in as little as a single generation in fishes, crustaceans and molluscs (Araki et al 2007;Araki and Schmid 2010;Christie et al 2012). Additionally, Holland et al (2022) recently demonstrated evidence of rapid selection in H. rubra following a single generation of exposure to disease. Considering the potential for rapid evolutionary responses, it might be expected that multiple generations of captive rearing would be sufficient for local adaptation.…”
Section: The Influence Of Provenance On Ct Maxmentioning
confidence: 99%
“…Previous studies have shown that adaptation to culture environments can occur in as little as a single generation in fishes, crustaceans and molluscs (Araki et al 2007;Araki and Schmid 2010;Christie et al 2012). Additionally, Holland et al (2022) recently demonstrated evidence of rapid selection in H. rubra following a single generation of exposure to disease. Considering the potential for rapid evolutionary responses, it might be expected that multiple generations of captive rearing would be sufficient for local adaptation.…”
Section: The Influence Of Provenance On Ct Maxmentioning
confidence: 99%
“…Although we know relatively little about the mechanisms underlying recovery (14,15), host evolution is one possibility (3,16). This process is known from a diversity of wildlife populations (17)(18)(19)(20), and often results in increased host resistance and/or tolerance (see 21, for definitions). However, linking these evolutionary responses to population recoveries is difficult and few clear examples exist.…”
mentioning
confidence: 99%
“…Science-based fishery management (SBFM) is a management framework where decision-making process is based on the best available science (BAS) (Ogawa & Reyes, 2021;Su et al, 2021) regardless of the strength and limitations of the methodologies implemented (reviewed by Breen, 1992): the pāua management system can be considered to be a sciencebased one. Nonetheless, given the increase in scientific literature on economically important species in New Zealand and especially genomics-based studies (Ashby, 2019;Koot et al, 2021;Holland et al, 2022;Papa et al, 2022, current thesis), the New Zealand fishery management system framework has potential to be reformed to integrate the use of this new type of data for pāua with the fishery data currently in use.…”
Section: Integrated Interpretation Of the Main Results And The Impact...mentioning
confidence: 99%
“…for what is now referred to as "fishery genomics" with the increasing number of molecular markers that can be employed and analysed at once (reviewed by Benestan, 2019). Despite the fact that finfish are still the most targeted taxonomic group for these studies (Reiss et al, 2009; reviewed by Benestan, 2019;Benestan et al, 2021;Bertram et al, 2022), the use of genomics has been successful in increasing information about biological units and suggesting reviews of stocks and management units for economically important molluscan species (e.g., Pecten novaezelandiae, Silva & Gardner, 2015;Pinctada margaritifera, Lal et al, 2016;Doryteuthis opalescens, Cheng et al, 2021;Buccinum undatum, Morrissey et al, 2022) and abalone species (Miller et al, 2014;Mejía-Ruíz et al, 2020;Mares-Mayagoitia et al, 2021, Holland et al, 2022.…”
Section: Fisheries Management Has Benefitted From Newly Developed Gen...mentioning
confidence: 99%